Translating Clinical Research into Practice: Practice-Based Research Networks—A Promising Solution. (1st March 2003) - Genel, Myron; Dobs, Adrian
Abstract : Greater effort is needed to translate research discoveries into clinical practice and to ensure that proven treatments are routinely implemented by physicians. Practice-based research networks are an undervalued resource in the endeavor to bring research results to bear in patient care. These networks are groups of practicing health care providers who have organized to address research questions of primary importance to their patients. Existing practice-based research networks have addressed a wide range of issues, including improvement of preventive service delivery, reliability of diagnostic measures, practice variation, disease prevention, and systems of care coordination. Several deficiencies in the current system prevent practice-based research networks from reaching their full potential as mechanisms of translating clinical research into practice. For practice-based research networks to flourish, they need increased funding for practice-based research networks; information systems to facilitate research by practicing physicians; training programs for health care providers; and communication networks between providers, clinical researchers, professional societies, and academic health centers.